DEVELOPING CHILDREN'S MEMORY IN MEMORIZING THE QUR'AN JUZ 30 USING TALAQQI METHOD FOR 5-6 YEAR-OLD CHILDREN AT TAMAN QUR'AN KINDERGARTEN BANYUWANGI - Habibah Afiyanti Putri; Riris Wahyuningsih; Fitriatul Masruroh (FORPIM PTKIS ZONA TAPAL KUDA, 2023)
Currently, the Al-Qur'an tahfidz is a popular superior program and preferred in Islamic-based educational institutions, including early childhood. But in reality, many early childhood still cannot read the Qur'an. For this reason, an appropriate method is needed to make the Qur'an memorizing easier. Talaqqi is a suitable method for learning to memorize the Qur'an. Taman Qur'an Banyuwangi is one of the kindergartens with the flagship tahfidz Qur'an program that applies the talaqqi method. This study aimed to determine the application of the talaqqi method and to find out the supporting and inhibiting factors of the talaqqi method. This study used a qualitative approach with basic research. Data analysis techniques were carried out interactively through four stages: data collection, reduction, presentation, and conclusion. This research was conducted at Taman Qur'an Kindergarten Banyuwangi. The subjects of this study were tahfidz teachers, school principals and 8 group B students of Taman Qur'an Kindergarten. The results of the final accumulation of this research, the rote development results of Taman Quran Kindergarten students in the 2023-2024 academic year with four basic competencies, the students in group A which totalled 10 students and group B 8 students get enhancement. With this achievement, group A students could memorize from the Annaba letter to the Al-Infitar letter. For group B students, 3 children had completed memorizing the juz amma, 1 memorized 3 juz, and for the other 4 students, on average, they could only memorize from Surah Annab' to Al-Balad. This method is supported by the existence of 2 factors, namely supporting and inhibiting factors.